An Analysis of Communication Between Pilot and Master for Berthing and Unberthing at Tanjung Intan Harbour Cilacap - Ario Hendartono; Retno Anggoro (Jurnal Maritim Polimarin, 2016)
All human societies are shaped by language, and language itself is shaped by society. Every social institution is maintained by language. Seafarer, government, education, the family, all are carried on with language. Almost all of our contact with others involves speaking.  People speak differently according to their background. Often, the social characteristic of one person can be determined from his speech, education, and even occupation. Also, they speak differently according to the actual circumstances they find themselves at a particular time. For seafarers to be able to communicative effectively, they need to be able to use and understand English in arrange of situations. Being able to use English means that the seafarer can combine the building blocks of language (grammar, vocabulary, phonology) to express himself clearly and appropriately in speech and writing. Being able to understand English means that the seafarer can interpret messages that he hears and reads correctly and can respond to these messages appropriately and comprehensibly. When a seafarer’s can demonstrate the ability to do this, he proves his communicative competence in English. Maritime communication comprises communication between vessels and coast stations, intership communication and intraship communication (internal communication when the vessel is berthing, casting off or un berthing, leaving berth, loading and discharging, etc). Vessels and coast stations can communicate by means of radio telephony, satellite, Digital Selective Calling (DSC) and radio-telex. The categories of messages that can be transmitted and received are called priorities. They indicate the importance of the message. In maritime communication has a specific communication for communicating between vessels and coast- stations, vessel and vessel called SMCP (Standard Marine communication Phrases).